The development of RNA logic gates library for the construction of molecular information processing circuits / Lee Yiling - Lee , Yiling (2016)
DNA, RNA and Protein are the computation devices of life. Accordingly, the plausibility of adapting these substrates into conventional machines has been actively investigated. Thus, various macromolecules devices have been developed. At its core, these devices can process physical or chemical inputs to generate outputs imitating conventional Boolean logical operators. This is feasible through the exploitation of allosterically controlled DNA enzymes (DNAzymes) and RNA enzymes (specifically, small catalytic RNAs). For instance, hammerhead ribozyme is an RNA enzyme that can undergo self-cleavage to produce two distinct products. It is allosterically controlled by introducing aptamers to facilitate the change of conformations from inactive to active states (i.e., catalytically inactive to active conformations) through self-assembly of input oligonucleotides. In this study, we investigate the plausibility of designing a programmable RNA circuit comprising of multiple YES-logical operators. We designed a library of RNA-YES gates, which can be integrated into an RNA circuit imitating a seven-segment display (SSD). Each circuit comprises ten logical operators that are organized into 13 wells (segments). Every YES-logical operator in the circuit will have its own unique oligonucleotide binding site (OBS) region (identifier) and will be activated only if the specific effector (input) is present. The current solution to design such system requires a stringent and highly customized algorithm. In this study, we are attempting to resolve this issue through utilization of simple heuristics. Three different strategies were investigated in developing the logic gate library. Each strategy corresponds to the different severity level of substituting specific regions of the logic gate sequences (from minimal to very loose) based on the dependency of each base (to be paired or unpaired) in the two meta-states. The operators are then subjected to a stringent in-silico filter cascade to ensure its workability in the laboratory. As predicted, substitution of bases must be controlled to ensure workability. However, this is subjected to some tolerances to allow the generation of adequate number of candidates. Random operators were selected and verified through wet-lab validation. By utilizing simple heuristics, we have managed to develop a comprehensive RNA logic gate library that is able to provide a large pool of plausible YES-gates for constructing molecular circuits capable of information processing tasks.